A carbon-rich nanofiber framework based on a conjugated arylacetylene polymer for photocathodic enzymatic bioanalysis. Issue 72 (23rd December 2019) - Tang, Junyan; Liu, Xiaoya; Yang, Chengwei; Zhang, Zhening; Sun, Rui; Li, Hongmei; Li, Caolong; Wang, Fei
Abstract : The metal-free photocathode fabricated by porous carbon-rich nanofiber framework of PTEB film realized "signal-off" photocathodic bioanalysis of glucose. Abstract : Poly(1, 3, 5-triethynylbenzene) (PTEB), a newly developed conjugated arylacetylene polymer, was utilized for photoelectrochemical (PEC) enzymatic bioanalysis in this work. The porous nanofiber framework of PTEB film which produced an apparent cathodic photocurrent under visible light illumination was fabricated on an indium tin oxide (ITO) electrode via copper-surface mediated interface Glaser polycondensation. As the photocurrent density of the metal-free photocathode displayed a characteristic O2 dependency, the consumption of dissolved oxygen caused by the modified glucose oxidase (GOx) in biocatalysis induced a depressed photoresponse in the presence of glucose. The fabricated PEC transducer exhibited favorable glucose sensing performances in the linear range of 5 μM to 8 mM and with the detection limit of 1.7 μM; it could also be employed in glucose monitoring in human serum. Moreover, the acetylenic carbon-rich polymer possessed the superior features of being cost-effective in preparation and machinable in device development, which sheds light on the exploration of an advanced PEC sensing platform based on conjugated organic polymers for the bioanalysis of valuable analytes.